The Influence of Work Environment, Rewards and Career Development on Employee Motivation (Study on IT Technology Service Company "PT XYZ" in Cilegon City) - Supriatna, Nana; Wahyuningtyas, Ratri (Journal of Economics and Business UBS, 2025)
In the rapidly evolving digital era, companies in the information technology sector must adapt to swift market changes. In this context, employee motivation becomes crucial, as low motivation can lead to a high rate of absenteeism, particularly unauthorized absenteeism. This study aims to identify and analyze the effects of the work environment, reward systems, and career development on employee motivation at PT XYZ in Cilegon City. The methodology employed is a quantitative approach. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) techniques. The research findings are expected to provide significant contributions to the understanding of the factors influencing employee motivation and how interventions in the work environment, reward systems, and career development can enhance motivation. Based on the results, it is recommended that PT XYZ implement strategies to improve the conditions of the work environment, reward systems, and more effective career development programs to boost employee motivation and performance. This study makes a significant contribution to the development of human resource management by emphasizing the importance of the work environment, reward systems, and career development in motivating employees. Practically, these findings can serve as a guideline for companies, particularly in the technology services sector. Therefore, it is recommended that organizations continue to enhance the quality of the work environment, implement transparent and fair reward systems, and provide structured and sustainable career development programs to maintain employee motivation and job satisfaction